2021
DOI: 10.33899/ijvs.2020.126662.1358
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive urolithiasis in domestic animals: An interplay between seasonal predisposition and dietary imbalance

Abstract: The present study was aimed to record and analyze the prevalence of obstructive urolithiasis in domestic animals like cattle, buffalo, horse, goat, sheep, dog and cat presented at RVP-TVCC, Indian Veterinary Research Institute. A total of 777 cases were reported during the academic session starting from April 2018 to March 2019 from Bareilly and its surrounding regions. Incidence were highest among ruminants 92.92% comparing to other domestic animals 7.08%. Among the different animal species, caprine were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Moreover, aspartate aminotransferase was also considered as an indicator for muscle degenerations, however, also liberated from other damaged liver cells. and, generally, the high levels of both enzymes in diseased animals have just been turned out and exposed to uncommon exercise (20)(21)(22)(23). Furthermore, the cardiac degenerations could always lead to an increase in the level of serum troponin I. which also can indicate in different diseases affecting animals such occurs in inflammation of pericardial and endocardial tissues, In the foot and mouth disease of cloven-footed animals especially the cardiac form, on the other hand, there was a good relationship between the magnitude of the troponin levels and the severity of histological evidence of myocardial damage was also reported which in general indicated that serum troponin will always reflect the approved scale in the clinical and laboratory diagnosis of cardiac muscle injuries (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aspartate aminotransferase was also considered as an indicator for muscle degenerations, however, also liberated from other damaged liver cells. and, generally, the high levels of both enzymes in diseased animals have just been turned out and exposed to uncommon exercise (20)(21)(22)(23). Furthermore, the cardiac degenerations could always lead to an increase in the level of serum troponin I. which also can indicate in different diseases affecting animals such occurs in inflammation of pericardial and endocardial tissues, In the foot and mouth disease of cloven-footed animals especially the cardiac form, on the other hand, there was a good relationship between the magnitude of the troponin levels and the severity of histological evidence of myocardial damage was also reported which in general indicated that serum troponin will always reflect the approved scale in the clinical and laboratory diagnosis of cardiac muscle injuries (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Cystolithotomy refers to the surgical opening made in the urinary bladder to remove the formed stones from the bladder. The formation of urolith has many etiological factors, and their chemical composition also differs according to the mode of formation (Sharun et al, 2021). However, there are mainly four types of mineral deposits in uroliths: Urate, cystine, struvite (magnesium ammonium phosphate), and calcium (Tion et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Obstructions are more common in males due to the narrower and longer penile urethra, which contains structures like the sigmoid flexure and vermiform appendix that increase the risk of obstructions. Early castration of young animals reduces the urethral diameter, thus increasing the risk of obstruction (Gazi et al, 2014, Sharun et al, 2021.…”
mentioning
confidence: 99%